2016
DOI: 10.1007/s00383-016-3873-6
|View full text |Cite
|
Sign up to set email alerts
|

Congenital H-type tracheoesophageal fistula: a national multicenter study

Abstract: H-type TEF is very rare and commonly presents with recurrent chest infection, chocking and coughing during feeds and cyanosis. Physicians caring for these patients should be aware of this and a high index of suspicion is of paramount importance to avoid delay in diagnosis with its associated morbidity. A contrast esophagogram is valuable in confirming the diagnosis. The study however may need to be repeated. Preoperative bronchoscopy is valuable to localize and cannulate the fistula for easier access during su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 28 publications
2
45
0
1
Order By: Relevance
“…The most common congenital esophageal malformation is esophageal atresia (EA), with the reported incidence ranging from one in 2500 to one in 3500 live births [ 34 , 35 ]. The outcome of the surgical repair depends mainly on the type of the EA, with up to 50% of those with an associated tracheo-esophageal fistula suffering from GERD [ 31 ].…”
Section: Clinical Presentation Of Gerd In the Pediatric Populationmentioning
confidence: 99%
“…The most common congenital esophageal malformation is esophageal atresia (EA), with the reported incidence ranging from one in 2500 to one in 3500 live births [ 34 , 35 ]. The outcome of the surgical repair depends mainly on the type of the EA, with up to 50% of those with an associated tracheo-esophageal fistula suffering from GERD [ 31 ].…”
Section: Clinical Presentation Of Gerd In the Pediatric Populationmentioning
confidence: 99%
“…Contrast studies are valuable in confirming a diagnosis, however, worth noting is that, in a recent multicentre study, <50% of cases were confirmed in a single contrast study 7. Contrast studies may give false-negative results and one review article reports statistically significant improvement in diagnostic accuracy with direct visualisation (tracheo/bronchoscopy) compared with an oesophagogram 8.…”
Section: Discussionmentioning
confidence: 99%
“…O procedimento consiste na laqueação e secção da fístula e pode ser realizado por toracotomia, cervicotomia ou toracoscopia. 19…”
Section: Atrésia Do Esófago Do Tipo Hunclassified